MITI and the Japanese miracle : the growth of industrial policy, 1925-1975 - Johnson, Chalmers, 1931-2010 (Stanford, California : Stanford University Press, 1982)
Annotation Positioning Statement: An explosive account of the resentments American policies are sowing around the world and of the payback that will be our harvest in the twenty-first century The hardcover received great review and media coverage. The author is incredibly well-connected and in constant demand as a speaker. The perfect match of author and subject.
The Japanese "Miracle" -- The economic bureaucracy -- The rise of industrial policy -- Economic general staff -- From the Ministry of Munitions to MITI -- The institutions of high-speed growth -- Administrative guidance -- Internationalization -- A Japanese model?
Includes bibliographical references (pages 367-380) and index.
Online resource; title from digital title page (viewed on May 18, 2020).
English.
eBooks on EBSCOhost
Keywords: Japan. -- Tsūshō Sangyōshō -- History; Japon. -- Tsūshō Sangyōshō -- Histoire; Japan. -- Tsūshō Sangyōshō; Japan -- Ministry of International Trade and Industry; Chōsen Kōgei Kenkyūkai; Japan -- Ministry of International Trade and Industry; Industrial policy -- Japan -- History; Electronic books; Politique industrielle -- Japon -- Histoire; Livres numériques.; e-books.; POLITICAL SCIENCE -- Public Affairs & Administration; Politique industrielle; Histoire économique.; Japon; Industrial policy; Japan; Industriepolitik; Industrie; Wachstum; Außenhandelspolitik; Japan; Industriepolitiek; Ministeries; Politique industrielle -- Japon; Japon -- Politique économique -- 1918-1945.; Japon -- Politique économique -- 1945-1989.; History